Adaptive immune protection of the middle ears differs from that of the respiratory tract - Dewan, Kalyan K.; Caulfield, Amanda; Su, Yang; Sedney, Colleen J.; Callender, Maiya; Masters, Jillian; Blas-Machado, Uriel; Harvill, Eric T. (Frontiers in Cellular and Infection Microbiology, 2023)
The efficacy of the adaptive immune system in the middle ear (ME) is well established, but the mechanisms are not as well defined as those of gastrointestinal or respiratory tracts. While cellular elements of the adaptive response have been detected in the MEs following infections (or intranasal immunizations), their specific contributions to protecting the organ against reinfections are unknown. How immune protection mechanisms of the MEs compares with those in the adjacent and attached upper and lower respiratory airways remains unclear. To address these knowledge gaps, we used an established mouse respiratory infection model that we recently showed also involves ME infections. Bordetella bronchiseptica delivered to the external nares of mice in tiny numbers very efficiently infects the respiratory tract and ascends the Eustachian tube to colonize and infect the MEs, where it causes severe but acute inflammation resembling human acute otitis media (AOM). Since this AOM naturally resolves, we here examine the immunological mechanisms that clear infection and protect against subsequent infection, to guide efforts to induce protective immunity in the ME. Our results show that once the MEs are cleared of a primary B. bronchiseptica infection, the convalescent organ is strongly protected from reinfection by the pathogen despite its persistence in the upper respiratory tract, suggesting important immunological differences in these adjacent and connected organs. CD4+ and CD8+ T cells trafficked to the MEs following infection and were necessary to robustly protect against secondary challenge. Intranasal vaccination with heat killed B. bronchiseptica conferred robust protection against infection to the MEs, even though the nasopharynx itself was only partially protected. These data establish the MEs as discrete effector sites of adaptive immunity and shows that effective protection in the MEs and the respiratory tract is significantly different. This model system allows the dissection of immunological mechanisms that can prevent bacteria in the nasopharynx from ascending the ET to colonize the ME.